COMPARISON OF PHYTOTHERAPY WITH ALPHA ADRENOCEPTERS BLOCKERS IN THE TREATMENT OF SYMPTOMATIC BENIGN PROSTATIC HYPERPLASIA - Ali, Liaqat; Hayat, Faiza; Opal, Samiullah; Khan, Saifullah; Khan, Qudratullah; Tariq, Kifayat (Journal of Postgraduate Medical Institute, 2020)
Objective: To compare the effectiveness of alpha blocker and phytotherapy in relieving the lower urinary tract symptoms (LUTS) in patients with Benign Prostatic Hyperplasia (BPH). Methodology: This randomized controlled trial was conducted in Department of Urology, Institute of Kidney Diseases, Peshawar from June 2017 to December 2018. A total of 308 patients, divided randomly in two groups, with 154 patients in each group, were enrolled using consecutive sampling. Group A received tamsulosin (alpha blocker) while patients in group B were put on Saw Palmetto as Phytotherapy. International Prostate Symptom Score (IPSS) and Uro-flowmetry were recorded before the therapy after 1st, 2nd, 3rd and 6th months respectively. A pre-designed proforma was used to enter the data, which was analyzed on SPSS version 20.0. Descriptive and inferential statistics were calculated where needed. Results: Mean age in group A was 65.1 ± 7.09 years, while group B showed 64.7 ± 8.01 years (p=0.442). The mean of IPSS before initiation of treatment in group A was 15.3 ± 3.02 and in group B it was 16.2 ± 3.04 (p=0.07), while post treatment IPSS at 6 months, in group A mean was recorded as 8.5 ± 7.4 and in group B it was 12.07 ± 2.75 (p=0.01). In Uroflowmetry, group A showed mean pre-treatment maximum flow as 8.4 ± 1.3 and in group B it was 8.2 ± 1.1 (p=0.064), while post-treatment maximum flow at 6 months for group A showed mean of 11.8 ± 1.5 and group B had 8.2 ± 1.1 (p=0.001). Conclusion: Alpha blockers are more effective than Phytotherapy in management of symptomatic BPH.